Diversity & inclusion in early childhood : an introduction - Devarakonda, Chandrika (Thousand Oaks ; SAGE, 2013)
"Covering a wide range of concepts and taking a broader perspective of what inclusion entail, this book offers an overview of current research, policy and practice in diversity and inclusion in the early years. It is a clear introduction to what inclusive practice means for those working with young children in the early stages of their lives. With case studies and activities designed to help students relate to diverse situations, the author discusses the main issues surrounding: race; gender; culture; disability and Special Educational Needs; English as an Additional Language; Traveller children; the contexts of inclusion and exclusion; good practice in early childhood settings; different perspectives of inclusion. This is essential reading for students studying inclusion and diversity on early childhood or early years courses, and those seeking to promote good practice and enable all children to develop to their full potential irrespective of their background."--Zadní strana obálky
Keywords: multikulturní výchova; integrovaná výchova a vzdělávání; děti; multicultural education; integrated education; children; studie; studies